Pengaruh Kualitas Pelayanan, Harga, Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Karaoke Keluarga Be Star Mmtc Pancing - Surbakti, Syamsul Bahri; Daulay, Akman; Sulastri, Obah (Manajemen dan Bisnis, 2024)
This research was conducted at the Be Star MMTC Pancing family karaoke which aims to determine the influence of service quality, price, customer satisfaction on customer loyalty at the Be Star MMTC Pancing family karaoke. The population in this study were visitors and customers at the Be Star MMTC Pancing Family Karaoke in Medan City who had visited. The sample used was 96 respondents. The sampling technique used was purposive sampling. The data used in this research is primary data. Research data was collected using quantitative methods with questionnaires, which have been tested with validity, reliability, classical assumptions and hypotheses. The data analysis technique in this research uses Multiple Linear Regression Analysis using the SPSS version 25.0 program. The research results show that both partially and simultaneously, the variables Service Quality, Price and Customer Satisfaction have a positive and significant effect on customer loyalty at Be Star MMTC Pancing Family Karaoke.